Stereoselective total synthesis of (-)-Depudecin - García-Ruiz, Cristina; Cheng-Sánchez, Iván; Sarabia-García, Francisco Ramón (ACS, 2015)
The total synthesis of the natural product depudecin, an antiangiogenic microbial polyketide with inhibitory activity against histone deacetylases, is reported. Characterized by a highly oxidized 11-carbon chain containing two epoxides conjugated through a trans-disubstituted olefin, its total synthesis was efficiently accomplished by a novel asymmetric methodology of epoxide formation based on a new class of chiral sulfonium salts, allowing for the construction of the oxirane rings in an efficient and stereoselective fashion.
Keywords: Polímeros; alcohols; aldehydes; amides; organic polymers; peptides and proteins